Predicting Hypnotic Use among Insomnia Patients with the Theory of Planned Behavior and Craving - Chien-Ming Yang; Yu-Shuan Lai; Yun-Hsin Huang; Ya-Chuan Huang; Hsin-Chien Lee (Behavioral Sciences, 2022)
While long-term hypnotic use is very common in clinical practice, the associated factors have been understudied. This study aims to explore the cognitive factors that might influence the long-term use of hypnotics based on the theory of planned behavior (TPB), and examines the moderating effect of craving between cognitive intention and actual hypnotic-use behavior at follow-up. A total of 139 insomnia patients completed a self-constructed TPB questionnaire to measure their attitude, subjective norm, perceived behavioral control, and behavioral intention of hypnotic use, as well as the Hypnotic-Use Urge Scale (HUS) to measure their craving for hypnotics. They were then contacted through phone approximately three months later to assess their hypnotic use. Hierarchical regression showed that perceived behavioral control was the most significant determinant for behavioral intention of hypnotic use. Behavioral intention, in turn, can predict the frequency of hypnotic use after three months. However, this association was moderated by hypnotic craving. The association was lower among the participants with higher cravings for hypnotic use. The findings suggest that the patients’ beliefs about their control over sleep and daily life situations, and their craving for hypnotics should be taken into consideration in the management of hypnotic use.